Metallurgy of a Ti–Au alloy synthesized by controlled electric resistance fusion; Intermetallics; Vol. 127 - Klimenov V. A. Vasily Aleksandrovich; Slobodyan M. S. Mikhail Stepanovich; Ivanov Yu. F. Yuriy Fedorovich; Kiselev A. S. Aleksey Sergeevich; Matrenin S. V. Sergey Veniaminovich (2020, 2020)
Title screen